Amateur photography - Menke, George Gerkein (My University, 1898)
Introduction: One great charm of photography is that it unites in the bonds of friendship men of all countries under the sun—their common helper. This, of course, is considering photography in its professional as well as its amateur, aspect. The latter being free from the money making taint, offers its champions a wide field for experiment and investigation, not possible in the field of professionalism. Indeed, all progress in photography can be traced to the labors of the enthusiastic student of this particular pastime. This fact makes it important that one should study the early history of photography and become familiar with its progress before he can consider himself an amateur in the truest sense of the word. Photography is an evolutionary science. The key to the proper comprehension of the present, lies in the past; and no man can afford to neglect the rich mine of experiences which is furnished by the works of his predecessors.
Citation: Menke, George Gerkein. Amateur photography. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Photography; History; Theses; Manuscripts (documents)